2001
DOI: 10.1083/jcb.200104099
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mammalian Chk1 during DNA replication arrest

Abstract: Checkpoints maintain order and fidelity in the cell cycle by blocking late-occurring events when earlier events are improperly executed. Here we describe evidence for the participation of Chk1 in an intra-S phase checkpoint in mammalian cells. We show that both Chk1 and Chk2 are phosphorylated and activated in a caffeine-sensitive signaling pathway during S phase, but only in response to replication blocks, not during normal S phase progression. Replication block–induced activation of Chk1 and Chk2 occurs norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
139
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(152 citation statements)
references
References 49 publications
(78 reference statements)
11
139
2
Order By: Relevance
“…As far as we are aware this is the first time such a checkpoint response has been documented. The molecular mechanism of replication slowing remains to be determined, however, Chk1 is known to be capable of suppressing replication origin firing (Feijoo et al, 2001;Zachos et al, 2003). This could provide a means of reducing the overall number of replication forks which are active at any one time during S phase in 5FU-treated cells, although effects on replication fork progression per se cannot be excluded on the basis of the current data.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…As far as we are aware this is the first time such a checkpoint response has been documented. The molecular mechanism of replication slowing remains to be determined, however, Chk1 is known to be capable of suppressing replication origin firing (Feijoo et al, 2001;Zachos et al, 2003). This could provide a means of reducing the overall number of replication forks which are active at any one time during S phase in 5FU-treated cells, although effects on replication fork progression per se cannot be excluded on the basis of the current data.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have established that Chk1 is required for multiple replication checkpoint responses including stabilization of stalled replication forks and suppression of latent replication origin firing, with the latter in particular representing a potential mechanism through which DNA synthesis could be blocked or slowed (Feijoo et al, 2001;Zachos et al, 2003). The close correlation between the activation of Chk1 by 5FU in WT DT40 cells and S-phase slowing suggested that the latter might be the result of an active checkpoint process rather than merely inhibition of DNA polymerase activity by dTTP depletion.…”
Section: -Fluorouracil-induced S-phase Slowing Is Chk1 Dependentmentioning
confidence: 99%
See 1 more Smart Citation
“…Whenever mammalian cells are prevented from completing synthesis from early replicons, ATM (ataxia telangiectasia mutated) independent, checkpoint signal stabilizes components of existing replicons and prevents initiation of replication from late-firing origins (Dimitrova and Gilbert, 2000). Chk1 responds to stalled replication forks as a necessary component for an intra-S phase checkpoint (Feijoo et al, 2001). Thus, one possibility is that DNA damage from incomplete replication initiation is responsible for activating p53 in the À/loxP cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although in all the cell types analysed up to now the checkpoint responses that lead to an intra-S-phase arrest have proved ATR-or Mec1-dependent (Santocanale and Diffley, 1998;Dimitrova and Gilbert, 2000;HekmatNejad et al, 2000;Feijoo et al, 2001), it would be interesting to know whether an ATR-independent response mutated in some cancer cells exists in mammals. This is also relevant to oncogenesis, as uncontrolled firing of origins also induces greater genomic instability (Tanaka and Diffley, 2002).…”
Section: Discussionmentioning
confidence: 99%